Pembuatan Minuman Herbal Air Serai Sebagai Minuman Kesehatan di Desa Gongsol, Kecamatan Merdeka, Kabupaten Karo - Ananda, Fitria; Prayogi Siregar, Aldian; Pranata Pardede, Joshua; Tazmi, Ayustia; Nadila, Shinta; Hilman Fikri, Muhammad; Mulyono , Hardi (Indra Institute Research & Publication, 2024)
The aim of this activity is to provide education on the manufacture and use of lemongrass plants as a drink rich in benefits, which is carried out in Gongsol Village. Providing simple education about the benefits of lemongrass and lemon drinks, where the content contained in lemongrass is able to reduce hypertension, control blood sugar, and strengthens the nervous system, as well as how to make it. The method used in this activity is to provide education about how to make and the benefits of lemongrass drinks to the Gongsol village community, as well as distributing ready-made lemongrass drinks to residents. The result of this service is that people who come to our service stand receive education about the benefits of lemongrass drinks, how to make them and ready-made lemongrass drinks.